Optimal Design of IIR Filters via the Partial Fraction Decomposition Method - Qi, H.; Feng, Z.; Yiu, K.; Nordholm, Sven (IEEE Circuits and Systems Society, 2018)
In this paper, we consider the minimax design of infinite impulse response(IIR) filter. First, we apply the partial fraction method to decompose the transfer function into a sum of low order fractions, as a result the minimax IIR filter design problem can be formulated with the stability condition as constraints. Second, among different possible decompositions of the transfer function, we prove that the second order decomposition can always achieve good approximation to the optimal solution. Based on the second order decomposition formulation, several numerical experiments have been conducted, and better IIR filters can be designed using the proposed method compared with existing methods in the literature.